Maximum diurnal trunk shrinkage is a sensitive indicator of plant water, stress in Diospyros kaki (Persimmon) trees - Badal, Eduardo; Buesa, Ignacio; Guerra, Diego; Bonet, Luis; Ferrer-Talón, Pedro J.; Intrigliolo, Diego S. (2017)
Persimmon tree (Diospyros kaki Lf) is a deciduous fruit tree included in the so-called group of minor fruit tree species Worldwide It is not widely grown but nowadays Kaki culture is of some importance in the south-east of Spain because of the high fruit commercial value Currently neither it is known about Kaki trees water needs nor crop responses to the irrigation regime The objective of the present research was to assess the feasibility of using maximum diurnal trunk shrinkage (MDS) as a plant water stress indicator for Kaki trees During two drought cycles in trees under either full or deficit irrigation the MDS obtained by means of LVDT sensors was compared with a reference indicator of fruit trees water status the midday stem water potential (Psi(stern)) In addition stomatal conductance and fruit diameter variations were also. followed As water restrictions began there was an immediate increase in MDS in correspondence with a decrease in Psi(stern) Pooling data from both drought cycles and irrigation regimes MDS and Psi(stern) were linearly correlated (r(2) = 0 77***) The magnitude of differences between well watered and deficit irrigated trees was much larger in the case of MDS than for Psi(stern) However the tree-to-tree variability of the MDS readings was three times higher than for Psi(stern) average coefficient of variation of 14% and 38% for 'Poem and MDS respectively Overall results reported indicated that MDS is a sensitive indicator of Kaki water status and it can be further used as an irrigation scheduling indicator for optimum irrigation management of this crop However the large MDS tree-to-tree variability should be taken into account when selecting the number of trees to monitor within an orchard.